In silico Study of Trianthema portulacastrum Embedded Iron Oxide Nanoparticles on Glycogen Synthase Kinase-3β: A Possible Contributor to its Enhanced in vivo Wound Healing Potential - Yadav, Ekta; Yadav, Pankajkumar; Verma, Amita (Frontiers in Pharmacology, 2021)
Trianthema portulacastrum Linn. (TP) leaves are traditionally utilized as a wound dressing material and it has rich amount of phenolic compounds. Oxidative stress and inflammation affect the Wnt/β-catenin pathway by modulating the glycogen synthase kinase-3β (GSK) activity subjected to delay in wound healing. The objective of the current study was to explore the wound healing effect of ferric oxide nanoparticles biosynthesized with fractionated TP extract (FeTP). The ability of TP active components (polyphenols) to inhibit the GSK was explored by using molecular docking studies. FETP were synthesized, characterized, utilized to prepare an ointment and its efficacy was investigated against full-thickness dermal wounds. Different wound healing parameters, level of enzymatic antioxidants, hydroxyproline content and tissue cytokines level were analyzed. Histopathology was performed to confirm the healing by newly formed tissue architecture. Rats treated with FeTP showed significantly swift healing with faster wound contraction rate, high tensile strength and hydroxyproline content along with the utilization of less time for epithelialization. Histopathological study also validated the potential wound healing effect of FeTP with complete re-epithelialization. The results of the present study cumulatively revealed that the green synthesized FeTP ointment approach may serve as a potential tool for dermal wound healing.